Present Status of Seagrass Ecosystem along Mandapam Coast with Special Emphasis on Anthropogenic Impacts. - Reshmi S. Raju (KUFOS, 2018)
Abstract- Seagrass ecosystem of Chinnapalam village of Pamapan coast, Gulf of Mannar region was studied. Transect line method was used for the biomass estimation. Hydrological parameters of nine stations were estimated. Study was conducted during the monsoon period (November, 2018). Salinity of the water column is 35 ppt. pH value ranges from 7.37 to 8.18. Dissolved oxygen showed a range of 2.70 mg/l to 8.64mg/l. The maximum concentration of nutrients such as phosphate, silicate, nitrite, nitrate observed during the study period was 0.065mg/l, 0.340mg/l, 0.012mg/l, 0.034mg/l respectively. And also anthropogenic activities on seagrass bed was analysed and management plans to conserve the resources have been suggested.